What Does the Board of Directors Do About Corporate Financial Reporting Through the Internet in Indonesia? - Djuminah, Djuminah; Rahmawati, Rahmawati; Amperawati, Endang Dwi; Kiswanto, Kiswanto (Indonesian Journal of Sustainability Accounting and Management, 2024)
The aim of this study is to examine the influence of the Board of Directors’ characteristics on corporate financial reporting through the Internet. The research employs multiple regression analysis to analyze the data. The findings indicate that gender, education level, educational background, and political connections significantly influence corporate financial reporting through the Internet among companies in Indonesia. However, the tenure of the Board of Directors does not have a significant impact. This study highlights the importance of the Board of Directors’ characteristics in corporate disclosure practices in Indonesia. Specifically, gender, education level, educational background, and political connections should be considered in the composition of the Board of Directors. Future research should explore this issue from a cultural perspective to gain a deeper understanding of the context surrounding the Board of Directors’ characteristics. The findings of this study contribute to minimizing agency costs, as timely disclosure of corporate financial information can reduce information asymmetry between principals and agents. This research provides valuable insights into sustainability management and accounting by emphasizing the role of corporate governance in enhancing transparency and accountability.